Education and Character Reformation in Nigeria Contemporary Society: Challenges and Prospects - Nwachukwu, Emmanuel Lucas; Azuka, Chukwuma Victoria (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Education is a transformative tool that is critical to the progress and development of a nation. The goal of true education is more than the cognitive development and creative thought processes. It is also about character molding of a person, making a holistic individual. It is true that the foundation of a quality education is character. An individual's education cannot be complete without character, and the knowledge they have acquired will not benefit Nigerian society or themselves unless their character is transformed. This study identifies character deficit as a major challenge in Nigeria contemporary society. The research examines the issues and prospects, and how education can be applied through character reformation to address the problems. To achieve the purpose of this study, qualitative method research is utilized. It relies on secondary data collected from text books, journal articles, and was analyzed in relation to the scope of the study (Nigeria). The theoretical framework is drawn from the social learning theory of Albert Bandura’s and moral development theory of Jean Piaget which set out the progressive model on how the Nigerian society can be morally re-engineered to produce citizens that will contribute to the progress and growth of Nigeria. It concludes and recommends that an integrative and consensus approach be adopted to achieve this objective.